Serological cross-reactivity between Crimean-Congo haemorrhagic fever virus and Nairobi sheep disease virus glycoprotein C - Maze, Emmanuel A.; Booth, George; Limon, Georgina; Belij-Rammerstorfer, Sandra; Tchakarova, Simona R.; Alexandrov, Tsviatko; Browning, Clare; Wilsden, Ginette; Ludi, Anna B.; Charleston, Bryan; Lambe, Teresa (Frontiers in Immunology, 2025)
IntroductionCrimean-Congo haemorrhagic fever virus (CCHFV) and Nairobi sheep disease virus (NSDV) are orthonairoviruses of concern, able to cause haemorragic fever disease in humans and sheep, respectively. CCHFV and NSDV cocirculating in small ruminant populations across South Asia and East Africa. Cross-reactivity to viruses of the Orthonairovirus genus can potentially interfere with serological assays when employed for serosurveillance in regions where two or more genus members overlap in their distribution.MethodsIn this study, sheep sera sampled from a region of confirmed CCHFV circulation and NSDV absence were utilized, thereby eliminating the possibility of co-exposure. Field sera were tested against in-house anti-NSDV ELISAs specific to the nucleoprotein (NSDV NP) and glycoprotein C (NSDV Gc) antigens as well as an in-house NSDV 80% plaque reduction neutralization test (PRNT80). We assessed whether there is a correlation between CCHFV- and NSDV-specific ELISAs. Furthermore, epitopes-derived from CCHFV antigens for sheep antibody that were available from the literature were analyzed.ResultsWhen comparing NSDV antigen-specific antibody responses against previously tested CCHFV antigen-specific antibody responses, a strong positive correlation was observed between the Gc-specific responses, while a weak positive correlation was observed between the NP-specific responses. Consequently, NP-specific ELISAs have a higher assay specificity compared to Gc-specific ELISAs, making them more suitable for serosurveillance in regions where multiple orthonairoviruses co-circulate. Crucially, only one seropositive sample to NSDV Gc-specific out of a set of 224 (0.4%) showed a neutralizing capacity at the lowest serum dilution (1:8), suggesting these field sera have not been exposed to NSDV. Based on an analysis of known epitopes in NP targeted by antibodies in sheep serum, we propose that NP is less cross-reactive because dominant epitopes are highly dissimilar between CCHFV and NSDV.DiscussionGc exhibited a strong cross-reaction while the NP was weakly cross-reactive due to dominant epitopes being highly dissimilar between CCHFV and NSDV. Our in-house PRNT80 assay can could be used as a confirmatory test in regions where CCHFV and NSDV circulate.